RECONSIDERING SOME CULTURAL CONSTRAINTS IN THE IMPLEMENTATION OF COMMUNICATIVE ENGLISH LEARNING - FX Nadar (Humaniora, 2000)
English is perhaps the most important foreign language in Indonesia . It is used for communication in business with other countries and studied in schools from junior high school to university level . People in Indonesia study English for different reasons . Many of them study English because if they understand English well they will be able to improve their general knowledge . Others particularly university students and lecturers study English because English may help them develop their academic achievement . Other people who are active in tourism and hotel industries need to study English because they have to communicate regularly with people from other countries . Despite the fact that English has been extensively studied, many learners feel they cannot use it for daily communication . This brief essay attempts to explore the constraints, particularly from the cultural views, which may have reduced the success of learning English . Approaches to language learning have undergone changes. Celce-Murcia (1991 :5- 8), for example, describes the stages of 20"-century approaches of language learning . In the sequence of approaches, communicative approach comes last . The origins of communicative language learning are to be found in the changes in the British language learning tradition dating from the late 1960's (Richards and Rogers, 1986 :64) which focus on the functional and communicative potential of the language . Richards and Rogers write (p .64) that with the interdependence of European countries 'the need to articulate and develop alternative methods of language learning was considered a high priority' . It seemed that since then the terms 'communicative' and also 'communication' became more and more popular (Atkinson, 1992 :6) . The implementation of communicative language learning in an EFL (English as a Foreign Language) context may cause problems . Paulston (1979 :3-4) describes the problems of non-native English teacher's imperfect proficiency, sociocultural values, class sizes, social behaviour, etc. which should all be taken into consideration . There may be constraints which reduce the effectiveness of its good values. This essay which views the possibility of implementing the communicative language learning and the likely cultural constraints in its implementation is divided into five main parts : firstly, the introduction; secondly, a glance at English learning in Indonesia; thirdly, communicative English learning ; fourthly, some constraints and how to minimize them ; and finally, the conclusion .